The Relationship Between Peak Take-off Force, Maximum Center of Mass Height, and Successful Block Performance in Volleyball Middle Blockers - Qadoori, Rafid; Abdulrahman, Ahmed; Ismaeel, Safaa (Pubmedia Jurnal Pendidikan Olahraga, 2026)
This study aimed to investigate the relationships between peak take-off force, maximum center of mass height, and blocking performance accuracy in volleyball middle blockers under different movement conditions. A biomechanical approach was adopted to analyze two players (youth and elite) using a force platform and motion capture system. Three experimental conditions were applied: static blocking, movement from the right side, and movement from the left side. Peak instantaneous leg force during the take-off phase and maximum center of mass height during flight were measured, alongside block accuracy scores. The results revealed that the elite player demonstrated consistently higher values in peak force, jump height, and blocking accuracy across all conditions. Significant positive correlations were found between peak force and maximum height, as well as between maximum height and blocking accuracy in all tests for the elite player. In contrast, the youth player showed significant correlations only when approaching from the right side, which was attributed to greater force production by the dominant leg, while non-significant relationships were observed in the static and left-side conditions. The findings indicate that peak take-off force is a critical determinant of vertical jump height, which in turn directly influences blocking performance. Additionally, asymmetry in force production between legs negatively affects performance consistency in less experienced players. In conclusion, enhancing lower limb explosive strength—particularly in both legs—is essential for improving jump height and blocking effectiveness in volleyball middle blockers.